Linear, Cyclical, and Spiral? History in Fourth-Century Greek Catechists - Huovinen, Harri (Vox Patrum, 2024)
This article delves into the previously underexplored conceptualizations of history articulated in the initiatory homilies of late fourth-century Greek catechists Cyril of Jerusalem and John Chrysostom. Grounded in their interpretation of the (Judeo-)Christian tradition, both authors conceive history as a divine narrative, constituting a coherent “history of salvation”. Metaphorically, their historical understanding can be illustrated as a spatial entity characterized through geometric imagery. A systematic analysis of their catecheses reveals that, fundamentally, both authors maintain a linear perspective on history, emphasizing divine beginning in creation and continuing through the present toward an eschatological consummation. Nonetheless, Cyril introduces more nuanced models, including cyclical depictions, notably a four-staged vision of paradise intertwined with a spiral-like conception of history. Owing seemingly to their primary objective of guiding audiences toward robust engagement with the Christian tradition and ecclesial participation, both authors refrain from addressing themes that might provoke unwarranted speculation. By presenting these insights, this article offers a novel contribution to the scholarship on late fourth-century theology of history, concurrently paving the way for historiographical exploration in modern scholarship of late antique Christian sources.